Felling induced dynamic stresses in some tropical hardwoods from Nigerian lowland rainforest (2011)
A study was undertaken to estimate the magnitude of dynamic stresses (MDS) induced in some mature tropical hardwood species during felling operation and their effect on the harvested wood. Five areas in Shasha forest reserve, Osun State, Nigeria were selected as the study sites because of the prevalent high. Two hundred and eighty nine trees represented by nine different species were studied. The species are Afzelia africana, Nauclea diderrichii, Terminalia superba, Khaya ivorensis, and Triplochiton scleroxylon Entandrophragma angolensis, Cordia milleniii, Mansonia altissima and Milicia excelsa. Using a checklist, information were collected on tree factors, terrain of the sites and experience of the operators. During felling of each tree, the duration of impact was estimated. Data collected were subjected to statistical analysis. The average content of the green wood ranged from 108% to 147% (dry basis) for all the species. The average impact force ranged from 1.498 X 106N to 7.588 X 106N, while the maximum dynamic stress ranged from 8.38 x 106 N/m2 for Triplochiton scleroxylon (Obeche) to 18.75 x 106N/m2 for Nauclea diderrichii (Opepe). The observed values of dynamic stress are very much higher than the ultimate static stress values for all the species and this will definitely affect the wood quality of the felled trees.